Approach in the modeling of wind turbines for power system stability studies and evaluation of their impact on electric power systems; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Razzhivin I. A. Igor Andreevich (2017, 2017)
Title screen